2000
DOI: 10.1046/j.1365-2532.2000.00272.x
|View full text |Cite
|
Sign up to set email alerts
|

The information needs and information seeking behaviour of family doctors: a selective literature review

Abstract: General practitioners play a central role in primary care. Clinical Governance and advances in Information and Communications Technology dominate the agenda for change. The aim of this literature review is to indicate publications that have made a significant contribution to understanding of the information wants, needs, behaviour and preferences of family physicians and to identify areas in which there is scope for further research. Concentrating on material published in the 1990s, this review looks at the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 14 publications
(19 reference statements)
0
19
0
Order By: Relevance
“…There is a large body of literature that demonstrates that nurses and other healthcare professionals prefer to use verbal information to support clinical decisions or resolve clinical uncertainty (Bryant , McKnight & Peet , Thompson et al . ,c, Estabrooks et al .…”
Section: Discussionmentioning
confidence: 99%
“…There is a large body of literature that demonstrates that nurses and other healthcare professionals prefer to use verbal information to support clinical decisions or resolve clinical uncertainty (Bryant , McKnight & Peet , Thompson et al . ,c, Estabrooks et al .…”
Section: Discussionmentioning
confidence: 99%
“…The model is now being used to investigate information behaviour associated with the provision of healthcare, as this is a fertile field for exploration (Coumou and Meijman, 2006;Davies, 2007;Dawes and Sampson, 2003;Gorman, 1999;Lacey Bryant, 2000). It is hoped that the findings will provide evidence of the practical relevance of the model and thus of the other models, and highlight any modifications that may need to be made.…”
Section: Conclusion and Further Researchmentioning
confidence: 99%
“…8 Their findings indicated that researchers were interested in consultation services, improved access to electronic journals, and training and support for basic computer skills and specific bioinformatics so ware tools. Other biomedically related groups that have been studied prior to implementing specialized services include medical researchers 9 ; clinical teams 10 ; health sciences faculty 11 ; biology faculty 12 and biology students 13,14 ; biotechnologists 15,16 ; family physicians 17 ; hospice and palliative care providers 18 ; and mental health service providers 19 …”
Section: May 2004mentioning
confidence: 99%